2020
DOI: 10.1186/s12889-020-08959-0
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy among participants from neighbourhoods with different socio-economic statuses in the southern region of Hungary: a pilot study

Abstract: Background Health literacy (HL) has a deep impact on people’s decisions about their health and health care system. Measurement and improvement of HL level is essential to develop an appropriate health care system. The aim of the study was to (1) conduct a pilot study among the population of Baranya County in Hungary with different socio-economic statuses, (2) evaluate the HL level and (3) found the correlations between socio-economic data, emergency departments’ visits, medical history and HL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(39 reference statements)
0
4
0
2
Order By: Relevance
“…In international studies, unhealthy behaviors (e.g., smoking) [ 16 ] and chronic diseases [ 44 ] are relevant for HL, contrary to our survey. The presence of a private physician at the place of study also appeared not to be relevant.…”
Section: Discussionmentioning
confidence: 82%
“…In international studies, unhealthy behaviors (e.g., smoking) [ 16 ] and chronic diseases [ 44 ] are relevant for HL, contrary to our survey. The presence of a private physician at the place of study also appeared not to be relevant.…”
Section: Discussionmentioning
confidence: 82%
“…CEE countries are less affected by inequalities in health related to ethnic origin or the status of immigrants (the problem is still the outflow of people to other countries [55]), but they are affected by inequalities related to low family well-being and uneven development of regions. Studies in adult population in Hungary on HL revealed that socio-economic status had a strong influence on HL level [56] and that the local deprivation affects academic performance [57].…”
Section: Discussionmentioning
confidence: 99%
“…A European Health Literacy Survey (HLS-EU) kutatása rávilágított, hogy az általuk vizsgált nyolc országban a lakosság majdnem 50%-a rendelkezik korlátozott egészségértéssel (17). Magyarországon korábbi kutatások alapján ezek a számok hasonló arányban oszlanak meg (23,24). Egy másik korábbi kutatás bizonyította az egészségértés és a Covid-19-tôl való félelem kapcsolatát, miszerint a magasabb egészségértési szinttel rendelkezôk kevésbé félnek a vírustól, a hozzá társuló fertôzéstôl (25), valamint ez a fajta tájékozottság a betegséggel kapcsolatba hozható depresszió ellen is védôfaktornak tekinthetô (26).…”
Section: Hungarian Translation and Psychometric Properties Of A Subje...unclassified